Increasing Students' Interest in Mathematics Through Some Real-Life Examples - Zulfikaharov Ilkhom Makhmudovich; Pulatov Mumin Muratali Ogli (Genius Journals, 2024)
In this article, taking into account the contribution of mathematics to the modern branches of science and technology, some real examples of the processes that can be used to increase students' interest in mathematics are highlighted.
Keywords: mathematics; what is mathematics; what kind of science is mathematics